"My Friend with HIV Remains a Friend": HIV/AIDS Stigma Reduction through Education in Secondary Schools—A Pilot Project in Buea, Cameroon. (7th February 2020) - Jacobi, Christoph Arnim; Atanga, Pascal Nji; Bin, Leonard Kum; Fru, Akenji Jean Claude; Eppel, Gerd; Mbome, Victor Njie; Etonde, Hannah Etongo Mbua; Bogner, Johannes Richard; Malfertheiner, Peter
The universal access to treatment and care for people living with HIV (PLWHIV) is still a major problem, especially in sub-Saharan Africa, where 70% of HIV-infected people live. Equally important is the fact that HIV/AIDS-related stigma is recognized to be a major obstacle to successfully control the spread of this disease. We devised a pilot project (titled "My friend with HIV remains a friend") to fight the HIV/AIDS stigmatization through educating secondary school students by openly HIV-positive teachers. In a first step, we have measured the amount and type of stigma felt by the PLWHIV in Buea/Cameroon using the "The people living with HIV Stigma Index" from Joint United Nations Programme on HIV/AIDS. Gossiping and verbal insults were experienced by 90% of the interviewees, while 9% have experienced physical assaults. Using these data and material from the "Toolkit for action" from the "International Centre for the Research on Women, " the teachers educated the students on multiple aspects of HIV/AIDS and stigma. The teaching curriculum included role-plays, picture visualizations, drawing, and other forms of interactions like visits to HIV and AIDS treatment units. Before and after this intervention, the students undertook "True/False" examinations on HIV/AIDS and stigma. We compared these results with results from students from another school, who did not participate in this intervention. We were able to show that the students taking part in the intervention improved by almost 20% points in comparison to the other students. Their results did not change.